Comparison of Methylene Blue versus Patent Blue Dyes in Sentinel Lymph Node Biopsy: A Prospective Study at A Tertiary Care Hospital - Javed, Ayesha; Naz, Saman; Syeda Rifaat Qamar Naqvi; Aqsa Saleema; Akram, Zohra; Naqvi, Syeda Saima Qamar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the diagnostic accuracy of Methylene blue versus patent blue dyes in the identification of sentinel lymph node (SLN) on biopsy, and compare clinical patient outcomes, including adverse effects and local tissue effects. Study Design: Quasi-Experimental study. Place and Duration of Study: Department of Breast Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Mar to Sep 2025. Methodology: A total 240 were divided to identify sentinel lymph node using Methylene blue (n=120) versus patent blue dyes (n=120). Primary variable studied was the diagnostic accuracy of both dyes in detection of sentinel lymph node compared with the actual histopathology report. Secondary variables studied were incidence and frequency of adverse effects between both groups. Results: Diagnostic comparison of Methylene blue compared to actual histopathology results showed a diagnostic accuracy of 90.0% while comparison of patent blue dye showed a diagnostic accuracy of 95.8%. Frequency of adverse effects showed that hypersensitivity was seen in 05(4.2%) versus 07(5.8%) patients (p=0.769), skin rash was seen in 04(3.3%) versus 08(6.7%) patients, bronchospasm was seen in 00(0%) versus 02(1.7%) patients (p=0.498), confusion was seen in 01(0.8%) versus 03(2.5%) patients (p=0.622), dizziness was seen in 02(1.7%) versus 05(4.2%) patients (p=0.446) and nausea was seen in 02(1.7%) versus 04(3.3%) patients (p=0.684). Conclusion: The study concludes that, combined with the radioisotope, both methods show comparable detection rates for sentinel lymph nodes with a favorable and comparable adverse effects profile.